2006
DOI: 10.5713/ajas.2006.1225
|View full text |Cite
|
Sign up to set email alerts
|

Animal Model Versus Conventional Methods of Sire Evaluation in Sahiwal Cattle

Abstract: A total of 1,367 first lactation records of daughters of 81 sires, having 5 or more progeny were used to evaluate sires by 3 different methods viz., least squares (LS), best linear unbiased prediction (BLUP) and derivative free restricted maximum likelihood (DFREML) method. The highest and lowest overall average breeding value of sires for first lactation 305 days or less milk yield was obtained by BLUP (1,520.72 kg) and LS method (1,502.22 kg), respectively. The accuracy, efficiency and stability of different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 7 publications
5
14
0
Order By: Relevance
“…All the product moment correlations between estimated sire merit calculated by different methods were also very high and ranged from 0.83 to 0.99 for OLS X BLUP, RLS X BLUP and OLS X RLS for APY, DPY, STAYAB and APY respectively (Table 4). Similar findings also reported by various researchers: Dalal et al (1999), Gaur et al (2001), Dubey et al (2006), Dhaka et al (2004), Banik and Gandhi (2006), Bajetha (2006), Mukherjee et al(2007), Kumar et al (2008) and Moges et al (2009). Rank and product moment correlations among sire merit calculated by various sire evaluation procedures for different production efficiency traits revealed that product moment correlations were comparatively higher than those of rank correlations barring few exceptions.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…All the product moment correlations between estimated sire merit calculated by different methods were also very high and ranged from 0.83 to 0.99 for OLS X BLUP, RLS X BLUP and OLS X RLS for APY, DPY, STAYAB and APY respectively (Table 4). Similar findings also reported by various researchers: Dalal et al (1999), Gaur et al (2001), Dubey et al (2006), Dhaka et al (2004), Banik and Gandhi (2006), Bajetha (2006), Mukherjee et al(2007), Kumar et al (2008) and Moges et al (2009). Rank and product moment correlations among sire merit calculated by various sire evaluation procedures for different production efficiency traits revealed that product moment correlations were comparatively higher than those of rank correlations barring few exceptions.…”
Section: Resultssupporting
confidence: 78%
“…Therefore, suitable selection criterion which gives best discrimination among sires should be formulated to evaluate sires on the basis of performance of their daughters considering both phase as well as stayablity life traits. To improve the efficiency and accuracy of sire evaluation programmes many sire indices has been developed by using the procedures of Least -Squares (OLS), Regressed Least -Squares (RLS) and Best Linear Unbiased Prediction (BLUP).The literature is dotted with conflicting reports Pundir et al (2004); Dhaka et al (2004); Banik and Gandhi, (2006) ;Raja, (2010) on comparative evaluation of various sire evaluation techniques in Murrah buffaloes. Therefore, an effort has been made to estimate breeding values for different phase and stayablity life traits by different methods in Murrah buffalo and comparison of these methods to find out the most suitable method for sire evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Large genetic variation was also observed between the estimated breeding values of sires by Dalal et al (1999), Dubey et al (2006) in crossbred cattle, Banik and Gandhi (2006) in Sahiwal Cattle; Kumar et al (2008) on Karan fries cattle and Moges et al (2009), Singh and Singh (2011 and Dubey and Singh (2014) in crossbred cattle.…”
Section: Resultsmentioning
confidence: 76%
“…CV was almost similar for BLUP-SM (22.89%) and BLUP-AM (21.35%) indicating that all these methods were almost equally stable. Banik and Gandhi (2006) however reported that the deviation of CV with respect to unadjusted data was lower in BLUP compared to LSQ indicating that BLUP method was more stable than LSQ.…”
Section: Coefficient Of Variationmentioning
confidence: 91%
“…Relative efficiency estimates were in agreement with the findings of Singh et al (2014) in Murrah buffalo. However, Banik and Gandhi (2006) in Sahiwal cattle reported the relative efficiency of BLUP in comparison to LSQ for 300-day milk yield to be 97%.…”
Section: Actual Milk Yieldmentioning
confidence: 98%